Solve for h f=10gh

Math
f=10gh
Rewrite the equation as 10gh=f.
10gh=f
Divide each term by 10g and simplify.
Tap for more steps…
Divide each term in 10gh=f by 10g.
10gh10g=f10g
Simplify 10gh10g.
Tap for more steps…
Cancel the common factor of 10.
Tap for more steps…
Cancel the common factor.
10gh10g=f10g
Rewrite the expression.
ghg=f10g
ghg=f10g
Cancel the common factor of g.
Tap for more steps…
Cancel the common factor.
ghg=f10g
Divide h by 1.
h=f10g
h=f10g
h=f10g
h=f10g
Solve for h f=10gh

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top